PENGARUH MARKETING MIX TERHADAP LOYALITAS NASABAH TABUNGAN PADA PT. BPR MUARO BODI - Saiful Anwar; Imron Eriyas Saleh (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to analize the effect of the marketing mix (product, price, promotion, place of people, physical evidence and process) on customer loyalty savings at PT. BPR Muaro Bodi. This research is a quantitative study. The data sources used in this study are primany data in the form of questionnaires and secondary data in the form of books and journals. The population used is 71 cuetomers who make savings books at PT BPR Muaro Bodi who where selected using accidental sampling, technical data analysis using. Instrument test, classical assumption test, multiple linear regression analysis and t test. The results of the study show that the product variable has a positive and significant effect on customer loyalty, the price variable has a positive and insignificant effect on curtomer loyalty, the promotion variable has a positif and significant effect customer loyalty, the place variable has a positif and significant effect customer loyalty, the person variable has a positif and notsignificant effect. Significant effect on customer loyalty, the physical evidence variable has a positif and significant effect on customer loyalty and the process variable has a positif and significant effect on customer loyalty